Linguistic and Cultural Specifics of Gratitude in Arabic Business Communication in English - L. A. Kochetova; Ya.Sh. S. Al-Bayati (Научный диалог)
The relevance of the study is due to the interest of linguistics in the problems of the functioning of the English language in various genres of business communication from the point of view of cultural linguistics. The results of a comparative study of the verbal formulation of the valuemarked communicative situation of gratitude in the corpus of English-speaking Arabic (Learner Business Letter Corpus (LBCL)) and English-American business correspondence (Business Letter Corpus (BLC)) are presented in the article. It was found that the linguistic means of expressing gratitude in the BLC corpus demonstrate great lexical and grammatical variability, preference is given to implicit performatives. It is noted that a limited set of lexical and grammatical constructions is used in the corpus of the Arabic English-language business communication, and explicite performatives dominate. It is shown that in both corpuses, gratitude is used to formalize a request or demand; in Arabic English communication, flattery acts as a variation of the speech act rethinking of gratitude. It was revealed that when expressing a proactive gratitude implying a request in the Arabic linguistic culture, strategies of positive politeness are used, demonstrating the unity of interests of the communication participants, in contrast to theAnglo-American linguistic culture, which relies on the strategy of negative politeness, softening impositivity.